2022
DOI: 10.21608/jssae.2022.125730.1063
|View full text |Cite
|
Sign up to set email alerts
|

Response of Two Potato Cultivars to Organic Fertilization and Potassium Foliar Application

Abstract: Potato cultivation is quite demanding and adequate fertilization is a key factor for maximizing yield and producing tubers of high quality. So, two variety of potato (Sponta and Lady Rosita) were used to evaluate its response to foliar application of two sources of potassium under organic fertilization during the two successive winter seasons of 2020/2021 and 2021/2022 at privet farm at Nabarouh city, El-Dakahlia Governorate under open field conditions. For this purpose, the experiment was laid out in split-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…Spraying Cara cultivar with KCit, followed by KTS increased number of tubers/ plant and total yield /ha., whereas spraying spunta cultivar with KCit, followed by Cara cultivar with KCit increased average tuber weight in both seasons. In the same line , (15) indicated that the highest average tuber weight, number of tuners/ plant and total yield /ha of potato were obtained with the interaction between spraying spunta cultivar and spraying with potassium silicate than spraying Lady Rosita cultivar with potassium silicate.…”
Section: Effect Of the Interactionmentioning
confidence: 79%
See 1 more Smart Citation
“…Spraying Cara cultivar with KCit, followed by KTS increased number of tubers/ plant and total yield /ha., whereas spraying spunta cultivar with KCit, followed by Cara cultivar with KCit increased average tuber weight in both seasons. In the same line , (15) indicated that the highest average tuber weight, number of tuners/ plant and total yield /ha of potato were obtained with the interaction between spraying spunta cultivar and spraying with potassium silicate than spraying Lady Rosita cultivar with potassium silicate.…”
Section: Effect Of the Interactionmentioning
confidence: 79%
“…Spraying Santana cultivar with KCit followed by KTS produced the tallest plants and recorded maximum value of shoot dry weight, whereas spraying at 90 days after planting in both seasons ( Table 2). Spraying Spunta, Santana , Cara, Lady Rosetta and Hermes with different sources of potassium , i.e., KCit, KSil, KF and KTS increased shoot dry weight/ plant compared to the same cultivars with control (spraying with water) in both seasons.In this regard, (15) showed that the interaction between spraying Spunta cultivar and spraying with potassium silicate showed a significant superiority in all vegetative growth, i.e., plant height , fresh weigh and dry weight / shoots than spraying Lady Rosetta cultivar with potassium silicate.…”
Section: Effect Of the Interactionmentioning
confidence: 94%